Customized housing design: Tools to enable inhabitants to co-design their house - Raposo, M.; Eloy, S. (Anthropologic: Architecture and Fabrication in the cognitive age - Proceedings of the 38th Conference on Education and Research in Computer Aided Architectural Design in Europe, eCAADe 2020, 2020)
In architecture, the individual needs and preferences of the end users need to be achieved in order to ensure a successful design. Standardized houses have been for long the reason for inhabitants' lack of satisfaction. The participation of inhabitants in the design process of their own houses is a crucial aspect to address housing customization, however there is a lack of effective tools to help inhabitants co-design their houses. Generative design solutions seem to be an effective way to address mass customization problem. In this paper we present a literature review on computer aided design systems that allow inhabitants to design, or partially design, their own houses. Existing solutions are classified in several categories (as generation process, target users, type of outcome, type of interaction, availability) regarding to what they accomplish and then analysed.